2022
DOI: 10.1186/s41935-022-00286-2
|View full text |Cite
|
Sign up to set email alerts
|

Global trends of suicidal thought, suicidal ideation, and self-harm during COVID-19 pandemic: a systematic review

Abstract: Background Suicide is one of the leading causes of death. The current systematic review is done to know the trend of suicidal thoughts, suicidal ideation, and self-harm during COVID-19 pandemic. Main text The search was done by using PubMed, ScienceDirect, and Google Scholar databases. With the help of Mendeley portal, articles were retrieved on the basis of inclusion criteria like to know the risk factors, vulnerable group, complete article PDFs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
5
0
3
Order By: Relevance
“…Even though the young population is one of the least vulnerable groups to a COVID-19 infection from a medical perspective, they seem to be most affected by the pandemic on a psychological level. Several studies support this assumption as they found increased levels of depression and anxiety ( Varma et al, 2021 ; Wang et al, 2021 ), substance use ( Horigian et al, 2021 ), and suicidal ideation ( Shobhana & Raviraj, 2022 ) in young people and students during the pandemic. A reason for these findings could be that young people and students were drastically affected by the restrictions during the pandemic.…”
Section: Discussionmentioning
confidence: 91%
“…Even though the young population is one of the least vulnerable groups to a COVID-19 infection from a medical perspective, they seem to be most affected by the pandemic on a psychological level. Several studies support this assumption as they found increased levels of depression and anxiety ( Varma et al, 2021 ; Wang et al, 2021 ), substance use ( Horigian et al, 2021 ), and suicidal ideation ( Shobhana & Raviraj, 2022 ) in young people and students during the pandemic. A reason for these findings could be that young people and students were drastically affected by the restrictions during the pandemic.…”
Section: Discussionmentioning
confidence: 91%
“…Based on these findings, we recommend that health practitioners be encouraged to assess for suicide ideation during follow-up visits among all rape survivors, specifically those who reported to have experienced TI and show signs of self-loathing. It is therefore crucial that all rape victims who report to have experienced TI during their ordeal to be assessed for early identification of SI as a global public health concern (ICD 10-CM) and the second leading cause of death worldwide [ 98 , 99 ]. This is especially so in Nigeria, where a study recently reported that the pooled prevalence of suicidal ideation was 9.8% and pooled suicide attempts was 16.2% annually [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…O que se argumenta é que o aumento de casos possivelmente pode se dar no desenrolar e até mesmo após o término das pandemias (Wasserman et al, 2020), o que torna importante que os profissionais da saúde estejam capacitados para o atendimento de novos casos. Outros estudos encontraram resultados contrários como estabilidade ou decréscimo em alguns subgrupos populacionais e elevação entre adolescentes e jovens, pessoas negras ou pardas, mulheres e idosos (Shobhana & Raviraj, 2022).…”
Section: [] Apertou Muito a Agenda Os Atendimentos Muito Espaçados En...unclassified
“…Apesar dos profissionais da saúde terem a percepção de que os casos de suicídio aumentaram durante a pandemia, evidências ainda são controversas sobre essa tendência em diferentes países e subgrupos populacionais (Pirkis et al, 2021;Shobhana, & Raviraj, 2022). No entanto, há uma estimativa de aumentos de casos após períodos de crise (Wasserman et al, 2020), demonstrando a necessidade de as organizações de saúde estarem atentas à capacitação desses profissionais de modo que se sintam melhor preparados para lidar com pacientes em risco.…”
Section: Considerações Finaisunclassified